Unlocking Employee Well-being in Tourism and Hospitality: A Systematic Literature Review - Nafees, Sehar; --, Sujood; Hamid, Sheeba (Journal of Tourism, Sustainability and Well-being, 2024)
In today's rapidly changing work landscape, ensuring a good balance between work and personal is a critical concern for employees. This equilibrium significantly influences their overall well-being, affecting work attitudes and behaviours. Research on the tourism and hospitality (T&H) workforce has covered many topics, but there remains an evident gap in scholarly investigations specifically addressing the well-being of employees in this industry. This work intends to fill the void by undertaking a thorough systematic literature review (SLR) focusing explicitly on employee well-being within the T&H sector. This thorough technique helped us identify and evaluate the most relevant studies from an extensive literature. The main goal of this academic paper is to address the identified research gap and provide practical insights for various stakeholders. Policymakers could benefit from recognising T&H workers' challenges and opportunities. Practitioners, including businesses in this sector, can gain valuable guidance on implementing strategies that promote work-life balance among their workforce. Scholars will also discover a consolidated resource that informs their future research and assists them in contributing to employee well-being discussions. Our results may also help T&H organisations develop work-life-balanced workplaces. Our rigorous literature analysis and practical insights seek to improve employee well-being, organisational performance, and industry vitality.